2023
DOI: 10.3390/plants13010057
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of the Impacts of Duckweed Coverage during Rice Growth on Grain Yield and Quality

Jingsheng Luo,
Shaowu Hu,
Tong Li
et al.

Abstract: The overuse and misuse of fertilizers have been causing duckweed outbreaks in irrigation ditches and paddy fields in many rice-growing areas. However, how duckweed coverage in a paddy field affects the rice yield and grain quality is under debate because duckweed may act as either a weed, competing with rice for mineral nutrients, or a “nutrient buffer”, providing significant ecological and economic benefits. To understand the effects of duckweed coverage throughout rice growth on the yield and quality of rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…How does DGP affect rice growth and yield formation? In our preliminary experiment conducted in concrete tanks filled with lotus-pond bottom soil, duckweed showed no significant impact on the grain yield of rice [27]. The result differed from most field experiment results [5].…”
Section: Introductionmentioning
confidence: 79%
“…How does DGP affect rice growth and yield formation? In our preliminary experiment conducted in concrete tanks filled with lotus-pond bottom soil, duckweed showed no significant impact on the grain yield of rice [27]. The result differed from most field experiment results [5].…”
Section: Introductionmentioning
confidence: 79%
“…Some previous studies agreed that duckweed introduction promoted rice yield through nutrient maintenance and delayed release [24,27] while other studies showed that duckweed as a typical weed outcompeted rice seedings in the race for nutrition [42,43]. But in a recent study, duckweed seemed to have more of a facilitating effect on rice grain quality than on yield [44]. Since there was no inhibition effect of duckweed on rice growth in the most competitive growth period (the first month) in this study, it is reasonable to assume that duckweed may have no negative effect on rice yield or even have a potential motivating effect after the duckweed residues release nutrients in the later period.…”
Section: Duckweed Growth and Weed Controlmentioning
confidence: 97%